Review of the theoretical underpinnings of loyalty programs - Henderson, Conor M.; Beck, Joshua T.; Palmatier, Robert W. (Journal of Consumer Psychology, 2011)
A review of the extant literature reveals that the theoretical underpinnings of the majority of loyalty program research rest on psychological mechanisms from three specific domains—status, habit, and relational. We propose that to understand how loyalty programs actually work, a broader, more holistic research perspective is needed to account for the simultaneous effects across these three theoretical domains as well as both cross‐customer and temporal effects. The contribution of this approach is a fresh research agenda advanced in 15 research propositions.